POTENSI Indigofera sp. SEBAGAI PAKAN KAMBING: PRODUKSI, NILAI NUTRISI DAN PALATABILITAS - Juniar Sirait; Kiston Simanihuruk; Rijanto Hutasoit (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Indigofera sp. is a potential legume to use as goat feed. The aim of this research was to study morphology, nutritive value, and palatability of Indigofera sp. that planted on 0.4 ha area at 1x0.5m2 plant-spaced. The research has conducted in lowland-wet climate agro-ecosystem at Goat Research Institute in Sungai Putih, Deli Serdang, North Sumatra, Indonesia. The fresh legume Indigofera sp. which harvested at seven months age and Leucaena leucocephala were fed to goats at the same time on palatability study. Twelve Boerka-goats were used in this experiment with average body weight 11.86±1.5 kg. The animals were allocated randomly into individual cages. The study of Indigofera sp. palatability has conducted for two weeks by competition system using L. leucocephala as the comparative. Data of dry matter intake were analysed using t-test. The result of this experiment showed that Indigofera sp. had good growth with high production and nutritive value. Fresh and dry matter productions at first harvest were 52 and 11 t/ha, respectively. Leaves proportion (36.4%) was lower than stem (63.6%). Crude protein content of Indigofera sp. was quite high (24.17%) based on dry matter. The palatability of Indigofera sp. was relatively similar with L. leucocephala. There was no difference of dry matter intake between Indigofera sp. (187.38±29.69 g/h/d) and L. leucocephala (193.85±21.53g/h/d). It was concluded that Indigofera sp. was a-high production and nutritive value; potential for goat feed.